The impact of religion on the evolution of cooperation and conflicts - Szocik, Konrad (Człowiek i Społeczeństwo, 2016)
Religion and religious beliefs have continued to play an important role in the evolution of the ability to cooperate at the level of large groups. It seems that natural selection favours selfishness rather than cooperative tendencies. Therefore, we suggest that cultural selection was necessary for the evolution of pro-social forms of behaviour. Cooperation is connected with conflicts, which are used to develop in-group cooperation. Here I show the possible impact of religion and religious beliefs on the development of an ability to cooperate, and to generate conflicts which are strictly connected with the possibility of in-group cooperation.